Makna Budaya Nama Motif Kain Bentenan Minahasa - Lahama, Silvana (Universitas Sam Ratulangi, 2015)
Bentenancloth is a Minahasa traditional fabric cloth which is the only craft of weavingfrom Minahasa people that has a very long journey of history. The existence ofthis cloth cannot be separated from the cultural and historical activities ofMinahasa tribe, where this cloth reflects the symbol of social status andbecome the part of life principal acted by the Minahasa people.Theobjectives of this research are to describe : 1) The name of motifs and lingualmeaning of BentenanÂ cloth, 2) Thecultural meaning behind the Bentenan cloth motifs.This research conduct in theform of qualitative-descriptive. The data taken from the books contains aboutthe history of Minahasa especially the Bentenan cloth, proposed by the formerresearchers and the culture expert of Minahasa. Fromthe result, it can be conclude that cultural meaning behind the name ofBentenan cloth motifs reflects the whole aspects of life especially theirbelieves on something considered being exist around them. The cultural meaningfromeach motifs carryingessential norm that people should know whether it isallowed to do and whether is not.KeyWords : The cultural meaning, The motifs in Bentenan cloth.